Equipping young minds: KIPPRA-CIP empowers youth in policy-making - Kirui, Leonard; Maru, Joyce; Saikah, Sheewa (CGIAR System Organization, 2024)
The youth bulge is a phenomenon common in many developing countries and Kenya is no exception. In Kenya’s demographic, the youthful population constitutes a higher percentage compared to other age groups, whereby 29% is between the ages 18 and 34. This youthful population has implications for the different aspects of society, it is therefore important to harness this potential for the country to achieve various developmental objectives. It would be remiss for policymakers not to tap into the potential of the youth to achieve national development and address societal challenges such as food and nutrition insecurity, income poverty, inequality, economic marginalization, and political challenges.